Trade secrets : the export answer book for small and medium-sized exporters : answers to most commonly asked international trade questions - International Trade Centre (Geneva International Trade Centre, 1998)
Handbook, customized to suit the needs of exporting enterprises in [country] and answering the most commonly asked questions related to the export process - covers market research, cultural issues, marketing, market entry methods, agents and distributors, trade shows, regulations, quality standards, pricing, financing and getting paid, transportation, documentation, packaging, and labeling, trade agreements, and provides contact information on in-country assistance organizations, and comprehensive listing of current publications, periodicals, software programs, and database available within [country], as relevant to small - and medium sized enterprise.&nbsp
I. Making the decision to export -- II. Preparing to export -- III. Finding the market -- IV. Finding the customer -- V. Cultural issues -- VI. Agents and distributors -- VII. Contracting -- VIII. Quality -- IX. Pricing -- X.  Financing and getting paid -- XI. Transportation and documentation -- XII. Packaging and labelling -- XIII. World Trade Organization (WTO) -- XIV. Importing
Keywords: Management of distribution (Marketing); EXPORT MARKETING; FOREIGN TRADE; TRADE PROMOTION; SMALL ENTERPRISES; MEDIUM ENTERPRISES; HANDBOOKS; MANUALS